Succession in woman-to-women marriages under customary law: a study of the Lobedu Kingdom - Maphalle, Kagiso Annette (Department of Private Law, 2018)
This study looks into the ways in which official customary law addresses succession complexities and legitimacy in woman-to-woman marriages. The social, political, cultural and legal background against which these marriages are concluded show the history of succession in woman-to-woman marriages and the position of women and children. The thesis highlights provisions of customary succession laws legislators sought to redress through the Reform of Customary Law of Succession and Related Matters Act 11 of 2009 and the Recognition of Customary Marriages Act 120 of 1998, which affect widowed spouses and certain children in customary marriages. The study uses literature review, case analysis and interviews to investigate the operation and legitimacy of woman-to-woman marriages, the benefits or harmful effects thereof, the background, context and history of the customary law of succession and acceptance of children in Bolobedu, and the application of living customary law. The study finds that woman-to-woman marriages are legitimate customary marriages under Lobedu customary law. It also finds that customary succession laws in such marriages have traces of patriarchy, although the community is under a matriarchal system of governance. It finds that the rule of male primogeniture is still applicable, and that women do not have a right to inherit from their deceased parents except at the discretion of the male heir. It finds that the acceptance of children in woman-to-woman marriages includes the performance of ceremonies symbolising the female husband's acceptance, and the child's use of her surname. It further finds that the application of official customary laws in Bolobedu is negligible, with the living customary law being the applicable law for all succession disputes. A further finding is the general lack of knowledge and understanding of succession rights under official customary laws by the community and their traditional leaders, who are aware only of provisions of the Lobedu living customary law which they readily provide. The study concludes that the legislators, judiciary and policy makers' lack of knowledge and understanding of woman-to-woman marriages and its accompanying succession laws inhibits and limits the adequacy of official customary law to regulate succession complexities. Rural communities' perceptions of their rights and knowledge of customary laws of succession, the practicality of provisions of official customary laws of succession, and their relatability to lived realities of rural communities further add to the inadequacy of official customary law.